State-Level Health and Economic Impact of COVID-19 in India - Deb, Pragyan (IMF Working Papers; Working Paper ;, 2021)
The health and economic impacts of COVID-19 on India have been substantial, with wide variation across states and union territories. This paper quantifies the impact of containment measures and voluntary social distancing on both the spread of the virus and the economy at the state level during the first wave of the COVID-19 pandemic. We construct a de-facto measure of state-level social distancing, combining containment strigency and observed mobility trends. State-level empirical analysis suggests that social distancing and containment measures effectively reduced case numbers, but came with high economic costs. State characteristics, such as health care infrastructure and the share of services in the economy, played an important role in shaping the health and economic outcomes, highlighting the importance of adequate social spending, health care infrastructure, and social safety nets.